Nitrogen-doped hollow porous carbon nanospheres coated with MnO2 nanosheets as excellent sulfur hosts for Li–S batteries. (26th October 2017) - Zhang, Xiaolong; Yang, He; Guo, Junling; Zhao, Shupeng; Gong, Shoutao; Du, Xinyu; Zhang, Fengxiang
Abstract: In this work, nitrogen-doped hollow porous carbon nanospheres coated with MnO2 nanosheets (NHPC@MnO2 ) were prepared as a novel sulfur host for the cathode of lithium–sulfur battery. N-doping of carbon and deposition of the inherently polar MnO2 promote chemical binding of the host with sulfur and its reduction products, known as polysulfides. Meanwhile, proper N-doping can improve the electron conductivity of carbon, and the nanosheet structure may help to guarantee facile electron- and lithium-ion transport through MnO2 . Attributed to these advantages, the NHPC@MnO2 /S cathode with a high sulfur content (70 wt% and 2.6 mg cm −2 ) exhibited an excellent cycle stability: its capacity retention was 93% within 100 cycles at 0.5 C. It also displayed a good rate capability: discharge capacities being ∼1130 mAh g −1 at 0.2 C, ∼1000 mAh g −1 at 0.5 C, ∼820 mAh g −1 at 1 C, and ∼630 mAh g −1 at 2 C. Our work demonstrates the synergistic effect of MnO2 nanostructure and N-doped carbon nanospheres for enhanced performance of lithium–sulfur battery cathodes.